A Space-Air-Ground Integrated Network Caching Method Based on Clustering Algorithm Content Popularity Prediction - Chao QIU; Chenyang WANG (天地一体化信息网络)
This paper proposed a new space-air-ground integrated network caching method, that was, cluster based content caching method.Based on the space-air-ground integrated network architecture, this method used the extracted content features to predict the popularity and used it for cache replacement decision.Content popularity prediction was realized based on dynamic clustering algorithm.This method could effectively reduce the pressure on the ground backbone network and further improve the quality of user experience.It evaluated the performance of our method using the open Douban movie review dataset.This dataset could be used to simulate user requests.Experimental simulation results showed the feasibility and effectiveness of the method.